2021
DOI: 10.2147/jpr.s302004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anti-Nerve Growth Factor Monoclonal Antibodies in the Control of Chronic Cancer and Non-Cancer Pain

Abstract: Nerve growth factor (NGF) belongs to the neurotrophin family and plays a fundamental role in the endurance of sensory and sympathetic neurons during embryogenesis. NGF, by interacting with tropomyosin receptor kinase A receptor (TrkA), modulates the pain pathway through the enhancement of the neurotrophic and nociceptor functions. Moreover, it has been demonstrated that NGF is upregulated in patients with chronic pain syndromes, which are difficult to treat. Thus, new non-pharmacological approaches, based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 64 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…In sum, anti-NGF antibodies are a promising therapeutic option in the treatment of OA, as they improve pain and function in patients; however, despite these benefits, meta-analyses of clinical trial data found that these agents increased the risk of neurological adverse effects (paresthesia, hypoesthesia, and peripheral neuropathy), being greater in patients treated with tanezumab than in patients treated with placebo and NSAIDs. Moreover, rapidly progressive osteoarthritis (RPOA) and fractures have been reported in some patients with hip/knee OA [ 51 , 84 ]; tanezumab-treated patients showed more joint safety events and total joint replacements [ 83 ]. RPOA was associated with higher doses of anti-NGF antibodies used alone or with NSAIDs, although the underlying molecular mechanism is unknown yet.…”
Section: Mabs In Osteoarthritis Painmentioning
confidence: 99%
“…In sum, anti-NGF antibodies are a promising therapeutic option in the treatment of OA, as they improve pain and function in patients; however, despite these benefits, meta-analyses of clinical trial data found that these agents increased the risk of neurological adverse effects (paresthesia, hypoesthesia, and peripheral neuropathy), being greater in patients treated with tanezumab than in patients treated with placebo and NSAIDs. Moreover, rapidly progressive osteoarthritis (RPOA) and fractures have been reported in some patients with hip/knee OA [ 51 , 84 ]; tanezumab-treated patients showed more joint safety events and total joint replacements [ 83 ]. RPOA was associated with higher doses of anti-NGF antibodies used alone or with NSAIDs, although the underlying molecular mechanism is unknown yet.…”
Section: Mabs In Osteoarthritis Painmentioning
confidence: 99%
“…Furthermore, the TrkA (NTRK1 gene) is exclusively expressed in the peptidergic DRG subpopulation. To note, it exhibits a high affinity for nerve growth factor (NGF) receptors [ 22 , 23 ]. NGF belongs to the neurotrophin family and plays a fundamental role in the differentiation and survival of neurons (including DRG) during embryogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…The NTRK1 gene (or TrkA) encodes for the neurotrophic tyrosine kinase receptor (NTKR) family. It binds NGF [ 23 ] and its mutations can lead to HSAN-IV (or CIPA). Several pieces of research focused on the NGF/TrkA signaling as a therapeutic target for pain [ 74 ] and other aims, such as anticancer actions [ 75 ].…”
Section: Research and Perspectivesmentioning
confidence: 99%
“…The mechanisms of NGF on the pain signaling pathway are complex, involving various other receptors and are in parts responsible for the development of neuropathic pain and pain modulation peripherally and in dorsal root ganglion. Anti-NGF mAb blocks NGF from binding to the tropomyosin-related kinase receptor (TrkA) and p75 neurotropin receptor (NTR), subsequently inhibiting the pain signaling pathway potentially treating and slowing down peripheral nerve sensitization ( 78 – 80 ). It has shown to provide OA pain relief over the period of about 4 weeks after a single subcutaneous injection.…”
Section: Treatment Guidelinesmentioning
confidence: 99%